Response of soybean genotypes introduced from South Korea to drought stress during reproductive stage - PURWANTORO PURWANTORO; SUHARTINA SUHARTINA; NOVITA NUGRAHAENI; APRI SULISTYO (Society for Indonesian Biodiversity, 2017)
Abstract. Purwantoro, Suhartina, Nugrahaeni N, Sulistyo A. 2017. Response of soybean genotypes introduced from South Korea to drought stress during reproductive stage. Biodiversitas 18: 15-19. Â Soybean is mostly planted in wetland (paddy field) during dry season. The plant is frequently suffered from drought which lead to low productivity. Cultivar tolerant to drought is needed in an attempt to increase productivity. Instead of high productivity, short duration and large seed size are soybean characteristics preferred by soybean farmers in Indonesia. Research aimed to assess response of soybean introduction genotypes to drought stress during reproductive phase were conducted during dry season of 2012. Genotypes used in the study were twenty soybean genotypes introduced from South Korea and three check cultivars (Mutiara, Grobogan, and Dering 1). The trials were conducted in the field at Kendalpayak Experimental Farm and under rain-shelter in Kendalpayak, Malang, East Java, Indonesia. Each genotype was planted in a single row of 2 m length, with no replication. Plant spacing was 40 cm x 15 cm. Fertilizers i.e. 100 kg ha-1 of Urea, 100 kg ha-1 of SP36, and 75 kg ha-1 of KCl were applied entirely at planting time. The plants were irrigated twice, at planting and at flowering time, and then subjected to drought stress during reproductive phase. Observations included days to flowering, days to maturity, plant height, number of branches, number of fertile nodes, number of pods, number of empty pods, weight of 100 seeds, and seed weight per plant. Results showed that five out of the 20 tested genotypes were resistant to drought stress during reproductive phase comparable to the check cultivar Dering 1. Four of them, i.e. Daewon, Ilmi, Jangmi, and Mausu, including large seed size and short duration. Those characteristics can be used to improve seed size and plants maturity of the existing drought tolerant cultivar.Keywords: Glyine max, introduction, genotype, drought stress, reproductive phase